STUDY OF WASTE GENERATION AND COMPOSITION IN THE TOURIST AREA OF BANDAR LAMPUNG CITY (CASE STUDY: KEDAI GUNUNG BALAU BANDAR LAMPUNG) - Falaguna, Berdo; Mufti, Aulia Annas; Kurnianingtyas, Erlina; Setiajaya, Arif (Sustainable Environmental and Optimizing Industry Journal, 2024)
The main problem in Kedai Gunung Balau Bandar Lampung is about waste management that is less than optimal, because the waste produced is just piled up and burned immediately. To anticipate waste problems that will cause pollution to the environment, it is necessary to make waste management efforts. Therefore, to plan a waste management system in the Kedai Gunung Balau Bandar Lampung Tourism Area, it is necessary to study the waste generation and composition at that location. The method used is waste sampling carried out for 8 consecutive days which refers to SNI 19-3964-1994. The results obtained are the average weight of waste generation per day of 25.620 kg / day and the average volume of waste generation per day of 0.945 m3 / day. The composition of waste generated consists of 11 types of waste in the form of organic and inorganic waste. The largest waste composition is food waste with a percentage of 19.528%.